(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
Abstract The purpose of this study is to show the working culture of the police in service to the community in Enrekang Police. The research method used is qualitative. The number of informants is seven. Data collection techniques through observation, interviews, literature studies. The results showed that the Enrekang Police Department in the implementation of the task of giving attention to habits, where the Enrekang Police Police always pay attention to the small details of errors in carrying out their duties. This is in line with the principle of obedience to the procedures for carrying out police duties. Enrekang Police Regulation as a party that provides public services to the community in order to provide maximum service, guided by the Code of Professional Ethics of the Police and Tri Brata and Catur Prasetya as the main duty of the police is to protect, serve and enforce the law and work in accordance with the Standards of Oprasional Procedures. Enrekang Police Department carries out tasks oriented to the values carried out by adjusting methods to the socio-cultural conditions of the community and providing examples first, be it institutionally, personally and close family of the Police so as to have a significant impact in the results of socialization and education to the community. Keywords: working culture, police, service